Teachers’ Readiness in Integrating Technology through TPACK-ICT Framework: Evidence from Papua, Indonesia - Tanta Tanta; Suriyah Satar; Nurbaya Nurbaya; Hanida Listiani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to analyze the level of Technological Pedagogical Content Knowledge in Information and Communication Technology (TPACK-ICT) skills among teachers in the Papua region, specifically in Keerom Regency, Jayapura Regency, and Jayapura City. A quantitative descriptive method was employed to examine teachers’ TPACK competencies. The research was conducted from May to August 2025 using an accidental sampling technique. The sample consisted of 31 elementary, junior high, and high school teachers from the three study areas who completed the questionnaire. The research instrument comprised 34 statements related to the TPACK framework, and the data were analyzed descriptively. The results reveal that teachers’ overall TPACK competence falls into the good category, with an average score of 3.63. The highest component score was found in Pedagogical Content Knowledge (PCK) at 3.93, followed by Pedagogical Knowledge (PK) and Technological Pedagogical Knowledge (TPK), both at 3.88. These findings suggest that teachers are relatively proficient in designing learning strategies that align with the subject matter and effectively integrate pedagogical and technological aspects. Meanwhile, the Content Knowledge (CK) and Technological Knowledge (TK) components scored 3.79 and 3.77, respectively, indicating a satisfactory understanding of subject matter and basic technological skills. However, these aspects still require enhancement, particularly in mastering more advanced technology and deepening content understanding. The lowest scores were recorded in Technological Content Knowledge (TCK) and the overall TPACK components, both at 3.63, showing that teachers continue to face challenges in fully integrating technology into learning content and combining technology, pedagogy, and content holistically. Overall, while teachers demonstrate strong pedagogical competence, further development in technology integration is essential to achieve optimal TPACK implementation.